Pencegahan korupsi melalui pendidikan karakter: Kebijakan dan praktik di Indonesia, Malaysia dan Singapura - Sujadi, Eko; Meditamar, Muhd Odha; Yandri, Hengki; Setiawan, M Eval (Jurnal Pendidikan Karakter, 2022)
Corruption is a serious problem for many countries in the world, especially developing countries. This systematic literature review (SLR) aims to analyze anti-corruption education in Indonesia, Malaysia, and Singapore from the aspects of policy and practice. The literature review model used is PRISMA which produces 70 articles that meet the inclusion and exclusion criteria. The analysis results show that anti-corruption education policies in the three countries are contained in written regulations, such as government regulations and regulations of the ministry of education. In addition, corruption eradication institutions in each country also make policies regarding corruption prevention through learning in schools and universities. The practice of preventing corruption through education in Indonesia and Malaysia is almost the same, namely through internalization of anti-corruption values into specific subjects, while Singapore places more emphasis on character education which is implemented using a particular curriculum. Even though the methods used are almost the same, Singapore is the country with the third-lowest level of corruption rate in the world. Legal products and their good application and high public awareness are the factors that influence them. Prevention of corruption is not enough only to be pursued by the government, but it needs the support of all parties, such as parents and society.